2000
DOI: 10.1093/humrep/15.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase start of low-dose FSH priming of follicles results in an efficient recovery, maturation and fertilization of immature human oocytes

Abstract: In this prospective study we investigated whether the maturation and fertilization of immature oocytes can be improved by administration of recombinant follicle stimulating hormone (rFSH) starting in the late luteal phase in two groups of women: group 1 (n = 6) women with regular menstrual cycles; and group 2 (n = 6) women with irregular cycles and polycystic ovaries (PCO) on ultrasound examination. Low-dose (37.5 IU) rFSH was commenced 11 days after LH surge during a spontaneous menstrual cycle and on the nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 25 publications
2
29
0
2
Order By: Relevance
“…Human chorionic gonadotropin (hCG) was the predominant medication used to induce oocyte maturation. Although four authors induced maturation with a GnRH agonist [10,[27][28][29], three authors used either hCG or GnRH agonist depending on the clinical scenario [11,30,31], and one author performed in vitro maturation following neither hCG nor a GnRH agonist [32]. All of the included studies reported the primary outcome of number of oocytes retrieved.…”
Section: Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Human chorionic gonadotropin (hCG) was the predominant medication used to induce oocyte maturation. Although four authors induced maturation with a GnRH agonist [10,[27][28][29], three authors used either hCG or GnRH agonist depending on the clinical scenario [11,30,31], and one author performed in vitro maturation following neither hCG nor a GnRH agonist [32]. All of the included studies reported the primary outcome of number of oocytes retrieved.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Eight of the qualitative studies were excluded due to the lack of a control group or due to a sample size of only one subject [8,10,28,32,[35][36][37][38].…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Granulosa cells of antral follicles are responsive to FSH and it is conceivable that administration of even small doses of this hormone may improve the follicle health status and increase the number and quality of retrieved oocyte. Between 1999 and 2000, this approach was initially tested in normovulatory and PCO women with results not always consistent (Suikkari et al, 2000;Mikkelsen and Lindenberg, 2001). A more recent study does not seem to demonstrate a clear advantage in the delivery of FSH to normovulatory women .…”
Section: Follicle Stimulating Hormone Primingmentioning
confidence: 99%
“…Accordingly, Lin et al (10) could not find any beneficial effect of FSH priming on the number of oocytes retrieved, maturation and fertilization rates. Conversely, Suikkari et al (11) reported that a small dose of FSH in women undergoing regular menstruation might increase the yield of immature oocytes collected. Junk et al (12) also demonstrated in their study in 2003 that FSH priming improves oocyte maturation, but does not have an effect on subsequent embryonic development.…”
Section: Discussionmentioning
confidence: 99%